Reaching new environments through illegal trade: evidence of a widely traded turtle in Colombia (2023)
ABSTRACT: A major threat to biodiversity is illegal trade, with many unwanted wildlife pets released into exotic environments outside their native distribution. Therefore, many potential invasive species have established in new ecosystems. Ecological niche modeling (ENM) has been used to predict and compare the environmental conditions of natural and exotic population in many groups. We used ENM to compare the climatic niche between natural and exotic areas of Trachemys venusta callirostris, one of the most traded turtles in Colombia. We generated a niche model using the MaxEnt algorithm through the R package kuenm to test several parametrizations and four sets of fresh water environmental predictors. Models were calibrated in the native distribution and projected to non-native zones in Colombia to identify suitable areas for the species. Further, we use a niche similarity test to compare native and exotic environmental space. We found few suitable areas within the projected zone even when using extrapolation; there was a greater suitability in the Magdalena River basin than in the Cauca River basin. Low similarity was detected between the niche comparison of native and exotic areas, suggesting that exotic populations have reached diferent environmental conditions than the native zone through ilegal trade. Although there was low extrapolation in the exotic area, the models projected ideal conditions in localities with new records for this turtle. The generalist strategies for feeding, thermoregulation, and reproduction in changing conditions may help this T. v. callirostris establish in new ecosystems, and with no current knowledge on dynamics between this exotic species and local fauna, its efects on aquatic communities are unpredictable